An Approach to Transform Chinese Historical Books into Scenario-based Historical Maps. (1st February 2013) - He, Li; Chen, Min; Lu, Guonian; Lin, Hui; Liu, Longyu; Xu, Jinfei
<x xml:space="preserve">Abstract</x> Spatio-temporal information (e.g. time, location, person and event) recorded in detail in vast Chinese historical books can provide evidence about the movement of entities (e.g. people, family, army and weapons) and their underlying spatial behaviours. Furthermore, this information largely reflects the process of social development, which makes it valuable to both professional research and public awareness. However, this information cannot be easily expressed and visually utilized because it is often hidden in the text of historical books. Aiming to better realize the potential value of such abundant information derived from historical books and bridging the gap between historical research and geographic space, a feasible and appropriate approach is explored in this article, to guide the transforming process from historical books to historical maps. The hope is that providing the scenarios of historical events will benefit related historical and social research. First, the integral framework of the approach was introduced, and the detail of building the specific spatio-temporal framework for information matching was discussed. Based on the spatio-temporal framework, the specification for the representation of historical books was designed. By extracting the spatio-temporal data from historical books, organizing them according to the specification and matching them with the spatio-temporal framework, the scenarios of historical events in the book (e.g. wars, migration, diseases, natural disasters, mass movement, etc.) can be visually transformed into historical maps. As the most critical writing of the Chinese Twenty-Four Histories, the Records of the Grand Historian (also known as Shiji) was employed as an example to test the proposed approach.